2010
DOI: 10.1017/s0047404509990662
|View full text |Cite
|
Sign up to set email alerts
|

Well, that’s why I asked the question sir”:Wellas a discourse marker in court

Abstract: This article discusses the use of well as a discourse marker in some New Zealand courtrooms. While well has been discussed by many in the past, the data have been selected mainly from small, friendly encounters of various kinds, including sociolinguistic interviews. The study reported on here looks at a very different situation that necessarily involves a range of relationships and includes both cooperative and adversarial activities. It confirms that explanations of well’s use focusing on single strands such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…witness examination stages). The use and functions of discourse markers during the evidentiary stage have been analysed in several studies (Innes 2010;Hale 1999Tkačuková 2010. In contrast, the focus of this article is on procedural stages (discussions between litigants in person, opposing counsels and judges about legal points and organisational matters).…”
Section: Previous Research On the Legal-lay Discourse In Courtroom Sementioning
confidence: 99%
See 2 more Smart Citations
“…witness examination stages). The use and functions of discourse markers during the evidentiary stage have been analysed in several studies (Innes 2010;Hale 1999Tkačuková 2010. In contrast, the focus of this article is on procedural stages (discussions between litigants in person, opposing counsels and judges about legal points and organisational matters).…”
Section: Previous Research On the Legal-lay Discourse In Courtroom Sementioning
confidence: 99%
“…The discourse marker 'well' is one of the most frequently studied discourse markers due to its versatile use and high occurrence in everyday conversation (Kim 2013;Jackson and Jones 2012;Lam 2010;Fuller 2003;Cuenca 2007;Schiffrin 1987;Svartvik 1980) as well as spoken interaction in institutional settings including interviews (Jackson and Jones 2012;Fuller 2003;Schiffrin 1987) and courtroom discourse (Innes 2010;Hale 1999). It has been studied as a turn-initial discourse marker occurring in all three positions: first pair part of adjacency pairs (Innes 2010;Hale 1999), second pair part (Innes 2010;Schiffrin 1987) and also third turn (Kim 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She claims that they "may assume specialized functions in certain types of discourse which may be partly or totally different from the ones described in existing studies of the same markers in conversational environments" (p. 338). We can see this in the use of well in television sportscasting (Greasley, 1994), the use of and to open particular types of questions in the medical consultation (Heritage and Sorjonen, 1994), the use of well and but in oral narrative (Norrick, 2001), the use of well in the courtroom (Innes, 2010), the use of okay in seminar talk (Rendle-Short, 1999), and the use of the Spanish discourse marker, bien, in the classroom (DeFina, 1997).…”
Section: Discourse Markers and Communicative Contextmentioning
confidence: 99%
“…The discourse marker, well, has been the subject of much research attention (Aijmer & Simon-Vandenberg, 2003;Blakemore, 2002;Cuenca, 2008;Garcia Vizcaino & MartinezCabeza, 2005;Innes, 2010;Greasley, 1994;Jucker, 1993;Lam, 2010;Norrick, 2001;Schiffrin., 1987;Schourup, 2001). Through this research, the meaning of the discourse marker well has been shown to be polysemous and elusive (Cuenca, 2008).…”
Section: Discourse Markers and Discourse Contextmentioning
confidence: 99%